Bagian Depan Vol.24 No. 1 (2022): February 2022 - Editor in Chief (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2022)
This section consists of Cover Page, Editorial Board Page, Peer Reviewer Page, Table of Content Page and Preface Page